LEGAL BASIS OF ORGANIZATION OF ACCOUNTING IN FARMS - A.M.Axmedov; I.B.Sapayev; A.A.Xaitboyev; O.Ch.Abdunabiyeva; M.B.Otaboyeva; S.O.Boltaboyeva; F.R.Allayarova; Sh.A.Bazarbayev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Farms should act as the basis of agricultural production organization. Because an economically free citizen, a true owner, is not only interested in effectively disposing of his property and increasing his wealth, but is also capable of enriching the entire country. In our country, with a deep study of the experience of foreign countries, very important measures for the economic reform of agriculture are being implemented, the introduction of market relations in the countryside and the development of the form of private ownership, the creation of legal, organizational and financial conditions for the support of the farming movement. It is no exaggeration to say that it is a decisive factor in achieving such high results.